Personnel policy of the Foreign Trade Department of the Ministry of Finance in the Kingdom of Poland in the years 1850-1862 - LATAWIEC, Krzysztof (Historia i Świat, 2021)
In 1851 the Kingdom of Poland was placed under the Russian customs jurisdiction, which resulted in the emergence of the Russian customs administration. For the system to function properly, the selection of appropriately trained clerical staff was needed. Moreover, the functioning of the customs administration in the consecutive years was only possible thanks to permanent full staffing of customs offices. The research into archival sources made it possible to analyze the personnel policy conducted in the Kingdom of Poland by the Foreign Trade Department of the Ministry of Finance in the Russian Empire. As it turned out, the customs administration, despite being Russian in structure, was dominated by clerks of Polish origin and Roman Catholic denomination. Furthermore, the Russian authorities tried to rely on employees experienced in working for the customs offices operating in the Kingdom of Poland before 1851.